Arabic Learning with Guided Composition Strategy for 7th Grade Students of Madrasah Tsanawiyah Thoriqul Huda Mojowarno Jombang - Abidin, Hasan (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Learning Arabic in elementary to tertiary educational institutions will equip students with four language skills, namely maharat al-istima’, al-kalam, al-qira’ah, and al-kitabah. Optimal skill acquisition cannot be separated from the appropriate method to be applied, because Arabic functions productively or expressively, namely to make others understand (al-ifham) through oral and written communication. Differences in learning backgrounds make students’ ability to write Arabic not yet well understood. Insya` muwajjah aims to train students’ initial stage abilities in writing Arabic. This study combines qualitative descriptive and eclectic methods. Data were collected through interviews and observations. The discussion of this article focuses on the application of Insya’ muwajjah (guide composition) in 7th Grade Students of Madrasah Tsanawiyah Thoriqul Huda Mojowarno Jombang. The results of the study show that the application of guided composition strategies can improve Arabic writing skills.